2010
DOI: 10.1007/s13238-010-0105-z
|View full text |Cite
|
Sign up to set email alerts
|

Snapshots of a hybrid transcription factor in the Hippo pathway

Abstract: The Hippo pathway plays key roles in animal development. It suppresses tumorigenesis by controlling the transcription of the target genes that are critical for cell proliferation and apoptosis. The transcriptional coactivator YAP is the major downstream effector of the Hippo signaling. Upon extracellular stimulation, a kinase cascade in the Hippo pathway phosphorylates YAP and promotes its cytoplasmic sequestration by 14-3-3 and ubiquitin-dependent degradation. When the Hippo pathway is turned off, YAP (which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…In this study, we found NHERF1 A190D mutation also appears to affect YAP function. The phosphorylation of YAP at serine 127 residue promotes its binding to 14-3-3 and impairs the nuclear import of YAP (37)(38)(39). NHERF1 A190D mutation led to a decrease in YAP phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found NHERF1 A190D mutation also appears to affect YAP function. The phosphorylation of YAP at serine 127 residue promotes its binding to 14-3-3 and impairs the nuclear import of YAP (37)(38)(39). NHERF1 A190D mutation led to a decrease in YAP phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Although YAP does not contain a DNA-binding domain, it binds to the TEAD family of transcription factors (which contains a sequence-specific DNA-binding domain) to form a functional hybrid transcription factor (Luo, 2010; Sudol et al, 2012; Zhao et al, 2008). The YAP–TEAD hybrid then activates the transcription of Hippo-responsive genes that promote cell growth and proliferation and inhibit apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…YAP is a major downstream effector of the Hippo pathway. It associates with the TEAD family of transcription factors to stimulate the transcription of Hippo-responsive genes that promote cell proliferation and inhibit apoptosis (Zhao et al 2008b;Luo 2010;Sudol et al 2012). Lats1/2-mediated phosphorylation inhibits YAP by promoting its cytoplasmic sequestration (Dong et al 2007;Zhao et al 2007;Hao et al 2008) and ubiquitination-dependent degradation (Zhao et al 2010b), thereby inhibiting the expression of Hippo-responsive genes, halting proliferation, and promoting apoptosis.…”
mentioning
confidence: 99%